2012
DOI: 10.1038/ijo.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet impacts endothelial function in nonhuman primate offspring

Abstract: OBJECTIVE The link between maternal under-nutrition and cardiovascular disease (CVD) in the offspring later in life is well recognized, but the impact of maternal over-nutrition on the offspring’s cardiovascular function and subsequent risk for CVD later in life remains unclear. Here, we investigated the impact of maternal exposure to a high-fat/calorie diet (HFD) during pregnancy and early postnatal period on endothelial function of the offspring in a nonhuman primate model. METHODS Offspring, naturally bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 49 publications
(64 reference statements)
3
84
1
3
Order By: Relevance
“…HFD offspring of this model display anxiety-like behavior [33] and increased vascular reactivity [16, 34], consistent with exposure to low levels of n-3 LCPUFA during fetal development [35, 36]. Though we found that resveratrol supplementation improves the ability of the HFD placenta to take up DHA, fetal n-3 LCPUFA levels in circulation remain low [27].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…HFD offspring of this model display anxiety-like behavior [33] and increased vascular reactivity [16, 34], consistent with exposure to low levels of n-3 LCPUFA during fetal development [35, 36]. Though we found that resveratrol supplementation improves the ability of the HFD placenta to take up DHA, fetal n-3 LCPUFA levels in circulation remain low [27].…”
Section: Discussionmentioning
confidence: 52%
“…Japanese macaques fed a diet composed of 35% fat, comparable to a typical western-style diet, before and during pregnancy have offspring born with fatty liver who develop obesity and vascular dysfunction in later life [15, 16]. Characteristics of these pregnancies include maternal insulin resistance, decreased uterine blood flow, decreased plasma LCPUFA levels, high placental triglycerides and placental inflammation [17], mimicking complications observed in pregnancies of obese women [1820], and possibly altering placental nutrient handling.…”
Section: Introductionmentioning
confidence: 99%
“…Given that obesity itself increases the risk of heart disease, cardiac dysfunction may be exaggerated in high-fat-fed offspring exposed to maternal obesity. Indeed, the combination of maternal HFD and post-weaning exposure to HFD culminates in reduced vasorelaxation in both mice and nonhuman primates (Fan et al, 2013;Torrens et al, 2012), with increased oxidative stress in the femoral arteries of adult male offspring (Torrens et al, 2012).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The research conducted with nonhuman primate models thus far suggests that the consequences of maternal HFD consumption and/or obesity during pregnancy generally have an adverse impact on a number of peripheral metabolic systems in both macaque (Fan et al, 2013; Grant et al, 2011; McCurdy et al, 2009; Suter et al, 2012a; Suter et al, 2012b) and baboon offspring (Farley et al, 2009; Maloyan et al, 2013). While the approach used to study diet-induced effects on central neuropeptide regulation and metabolic systems is quite informative, what is understudied is whether the maternal feeding phenotype is transmitted to the offspring.…”
Section: Regulation Of Food Intakementioning
confidence: 99%